Reka bentuk model kepimpinan berkesan institusi pendidikan tinggi Majlis Amanah Rakyat / Norazizah Che Mat - Norazizah , Che Mat (2018)
An excellent education institution is generally led by effective leaders. Thus, this study was aimed at developing an effective leadership model of higher education institutions for Majlis Amanah Rakyat. The design of this model involves three phases: first, the needs analysis phase was to identify the importance of doing this study. The second or design phase was to build a model based on a high level of consensus among experts, while the evaluation phase was to evaluate the prototype model built in the previous phase. Data collection was based on the three phases. First, the needs analysis involved qualitative methods with interviews of ten leaders of the organization; for the design phase, 15 local experts in the leadership field involved in the four-session Delphi study were consulted. In the evaluation phase, the prototype model was evaluated on the basis of questionnaire distribution to 240 academic staff in the higher education institutions of Majlis Amanah Rakyat. In addition, qualitative data from open-ended questions were collected for analysis. The quantitative data were analyzed using SPSS version 20.0 that involved descriptive statistics such as mode, median and Inter Quartile Range and inferential statistics such as Kruskall Wallis test. The findings of the first phase of this study need to be implemented when all participants complied with the design of the model as a guideline. This study also found seven effective leadership domains, namely: Leaders Who Care, Caring Leaders, Best Connection Leaders, Clear Leaders for Particular Purpose, Competent Leaders, Wise Leaders and Leaders Who Know The Goals. The model was designed based on high level of consensus with median scores more than 4 and Inter Quartile Range less than 1. Next, as a result of the study, the evaluation found the effectiveness of leadership was high when the mean score was more than 4.0. The study also found significant differences in terms of effective leadership among higher education institutions of Majlis Amanah Rakyat (p value below 0.05). The implication of this study is to highlight the importance of a model based on the consensus of local experts.